ANALISIS PENDAPATAN MASYARAKAT EKS-PELAKU ILLEGAL LOGGING DI DESA MAYAK KECAMATAN MUARA PAWAN KABUPATEN KETAPANG - Hardiansyah, Gusti; Husni, Harnani (Universitas Tanjungpura, 2013)
The society around the forest generally depends on the forest to extract their daily needs by taking the result of forest like timber and non-timber products for sale. However, since 2006 the illegal logging activity has been curbed and gave an impact to the communities livelihoods around the forest which caused the decline in their income. The objective of the research is to find out the alternative livelihoods after the controlling of the illegal logging, to determine the size of the income of the people before and after the controlling of illegal logging is executed, and to see the factors that is expectedly has an influence on the people's income. This research was conducted using a descriptive survey method with interview techniques. The result of the research showed that the occupations of the people before the controlling of illegal logging are tree feller/penebang, rafting agen/pengengkut, and log collector agent/pengepul. After the controlling, their changes their occupation as rice farmers,rubber farmers, fisherman, traders and rattan collectors. The peoples income before the controlling of illegal logging are; as much as 7 respondents have the lowest-income, that is less then Rp. 11.912.661, as much as 51 respondents have middle-income between Rp. 11.912.661-Rp. 21.284.645, and as much as 2 respondents have the higher-income, that is more than Rp. 21.284.645. While the incomes of the former of illegal loggers are as many as 9 respondents has high-income, > Rp. 26,337,189, -/year. And as many as 45 respondents have middle-income between Rp. 7.488.064, - Rp. 26.337.189, -/year. Then as many as six respondents have the lowes-income, that is below Rp. 7488064, -/year. Based on Chi-Square statisticsThere was no relationship between the level of income with the attitudes, people perceptions about the illegal logging activities. Keywords: Illegal Logging, Ex-Actor Illegal Logging, community income.